2011
DOI: 10.1371/journal.pone.0026557
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Extracellular Matrix-Mediated Pathways in Single-Suture Craniosynostosis

Abstract: Craniosynostosis is a disease defined by premature fusion of one or more cranial sutures. The mechanistic pathology of single-suture craniosynostosis is complex and while a number of genetic biomarkers and environmental predispositions have been identified, in many cases the causes remain controversial and inconclusive. In this study, gene expression data from 199 patients with isolated sagittal (n = 100), unilateral coronal (n = 50), and metopic (n = 49) synostosis are compared against both a control populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
2
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 69 publications
3
57
2
4
Order By: Relevance
“…Recently, transcriptomic analysis has identified differential gene expression in both SSC osteoblasts and controls (Stamper et al, 2011). Furthermore, these differences in the correlation structure of the transcriptome have shown upregulation of IGF1 activity in calvarial SSC osteoblasts (Stamper et al, 2011). In this study, SSC osteoblasts with elevated IGF1 expression were observed to have higher traction forces than controls.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Recently, transcriptomic analysis has identified differential gene expression in both SSC osteoblasts and controls (Stamper et al, 2011). Furthermore, these differences in the correlation structure of the transcriptome have shown upregulation of IGF1 activity in calvarial SSC osteoblasts (Stamper et al, 2011). In this study, SSC osteoblasts with elevated IGF1 expression were observed to have higher traction forces than controls.…”
Section: Discussionmentioning
confidence: 52%
“…This suggests that IGF1 influences migration and contributes to the development of SSC. In our previous study (Stamper et al, 2011), we demonstrated that differential IGF1 signaling results in upregulation of ECMmediated focal adhesions. Moreover, IGF1 signaling has also been implicated in mediating focal adhesion formation and cell migration (Manes et al, 1999;Andersson et al, 2009).…”
Section: −4mentioning
confidence: 81%
See 3 more Smart Citations